2017
DOI: 10.1002/ps.4609
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effect of selection with deltamethrin on biological parameters and detoxifying enzymes in Aedes aegypti (L.)

Abstract: Alterations in life parameters could be due to the accumulation of noxious effects or deleterious genes related to detoxifying enzymes, specifically those coding for mixed-function oxidases, along with the presence of recessive alleles of the V1016I and F1534C mutations, associating deltamethrin resistance with fitness cost in Ae. aegypti. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…In the absence of insecticide applications, resistance alleles can result in energetic costs or fitness disadvantages in comparison with its susceptible counterparts. Attempts to register fitness costs due to insecticide resistance are often based on the selection of insects in the laboratory for increased resistance or on backcrosses with laboratory strains to produce lineages differing only in the resistance traits [ 11 , 28 30 , 48 , 49 ]. This approach supposedly enables more accurate measures of changes on the fitness parameters related specifically to insecticide resistance rather than other genetic differences.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of insecticide applications, resistance alleles can result in energetic costs or fitness disadvantages in comparison with its susceptible counterparts. Attempts to register fitness costs due to insecticide resistance are often based on the selection of insects in the laboratory for increased resistance or on backcrosses with laboratory strains to produce lineages differing only in the resistance traits [ 11 , 28 30 , 48 , 49 ]. This approach supposedly enables more accurate measures of changes on the fitness parameters related specifically to insecticide resistance rather than other genetic differences.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ♀:♂ of the CRR was higher in � 21 d than in > 21 d, but of the CSS was no obvious difference between in � 21 d and > 21 d (S3 and S4 Tables). The other pyrethroids resistance studies in Musca domestica and Aedes aegypti showed an obvious fitness costs but no effects on sex ratio [14,33]. However, in the CRR, ♀:♂ was lower no matter in � 21 or � 30 d life table in comparison with the ones in the CSS and also appeared an age-specific reduction (Figs 1 and 2 Table), which meant beta-cypermethrin resistance caused a significant effect on sex ratio in houseflies.…”
Section: Fig 2 Comparisons Of the Life-history Trait Values Between mentioning
confidence: 84%
“…A lambda-cyhalothrin-resistant strain of houseflies showed only 26% fitness in comparison with that of susceptible strains [14]. Under deltamethrin selection pressures, Aedes aegypti fitness decreased by 41% [33]. Diflubenzuron resistance in an Aedes aegypti field population was associated with a fitness costs [34].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Resistance to pyrethroids in mosquitoes have been widely associated with the F1534C (21, 23, 25, 27, 29, 30, 32, 3941, 83, 88101) and V1016I mutations (24, 25, 27, 29, 30, 32, 36, 38, 40, 41, 88, 93, 97, 100, 102, 103). The simultaneous presence of both mutations has been associated with enhanced tolerance to deltamethrin in the past (31).…”
Section: Discussionmentioning
confidence: 99%